A 3–D wind and temperature pre–processor for ATD models. (4th August 2014) - Morselli, M.G.; Calori, G.; Finardi, S.; Mazzola, C.
Many atmospheric transport and dispersion models, based on various approaches and applied to different spatial scales, need 3–D meteorological fields referred to regular grid systems. Data generally available, however, cannot be directly employed because of their irregularities, inconsistencies, insufficient spatial detail or inadequate terrain representation. To fill the gap between these input requirements and the practical availability of data, a meteorological pre–processing system has been set up to provide 3–D fields on the basis of measured data available inside a selected area. The system allows, for a given area, (i) extraction and smoothing of elevation data from a digital elevation model; (ii) extraction of data from different meteorological databases; (iii) interactive selection and correction among the available measurements; (iv) interpolation in time of missing data; (v) data interpolation on a selected computational grid and (vi) reconstruction of 3–D temperature and mass–consistent wind fields. The whole system is outlined and a couple of applications at different spatial resolutions are presented.